PERBEDAAN HASIL BELAJAR ANTARA SISWA LAKI-LAKI DENGAN SISWA PEREMPUAN DALAM MATA PELAJARAN MATEMATIKA DI SDN SUNGAI RAYA 1 KECAMATAN SIMPANG EMPAT KABUPATEN BANJAR - Nadya Huda (Universitas Achmad Yani Banjarmasin, 2019)
Physiological and psychological factors can cause differences in student achievement. The presence of psychological factors in learning, will contribute quite important. This includes gender which is a sociocultural and psychological dimension Of men and women. The problem raised in this study is whether there are differences in learning outcomes between male and female students in mathematics in SDN Sungai Raya 1, Simpang Empat District, Banjar Regency. The study was conducted with the aim of finding out the differences in learning outcomes between male and female students in mathematics in SDN Sungai Raya 1, Simpang Empat Subdistrict, Banjar District. Sungai Raya 1 Primary School, Simpang Empat Subdistrict, Banjar Distri was made a place of research, while the object was the difference in learning outcome between male and female students in mathematics, while the subjects were students at SDN Sungai Raya 1, Simpang Empat Subdistrict, Simpang Empat District, Banjar District. The study population was all students of SDN Sungai Raya 1, Simpang Empat Subdistrict, Banjar Regency with a total of 120 students and the sample was determined using the Proportionate Stratified Random Sampling technique with 3 sample of 92 students. The research method used is descriptive method, while the data minig tool is a document. Where the learning outcomes of male students who have been converted into interval data is symbolized by X_1 and female student learning outcomes are symbolized by X_2. Based on the results of statistical analysis through t-test calculations obtained: toount of 3.023 lebih besar ttable of 1.986 with a significance level of 5% and df 90 means an alternative hypothesis that reads,